Frequency of Upper Body Muscular Demands in Contemporary and Ballet Dance Performance: A Cross Sectional Performance Analysis. - Farmer, Claire; Brouner, James (Journal of Dance Medicine & Science, 2025)
Introduction: There is currently little research relating specifically to the muscular strength and endurance requirements of the upper body such as lifts at varying heights, ground floor contact with the hands and inversions such as handstands. Enhanced understanding of muscular demands can inform training program design to build physical tolerance to meet the demand of the activity. The aim of this study was to ascertain the frequency of upper body muscular skills in contemporary and ballet dance performance. Methods: Analysis of 46 individual ballet performers (F = 23, M = 23) from 12 performances (duration 63.5 ± 44.5 minutes) and 44 individual contemporary performers (F = 21, M = 23) from 12 performances (duration 35.7 ± 4.3 minutes) was carried out. Frequency of upper body skills was recorded using Dartfish Easytag-Note and converted to mean frequency per minute of total performance and per performance by genre and by sex. Differences in frequency between genre were analyzed via Mann–Whitney U. Phase two analyzed differences between sex via Mann–Whitney U. Finally, analysis of differences between sex within dance genre was carried out via Wilcoxon signed rank test. Significance was accepted at P <.05. Results: A significant difference was apparent between ballet and contemporary dance for holding own weight (P <.05) with a greater total mean frequency within contemporary performances of 8.50 ± 9.03 compared to a total mean frequency of 1.51 ± 3.13 within ballet performances. Additionally, there was a significant difference for above shoulder assisted lift (P <.05) when comparing male dancers, with male contemporary dancers carrying out significantly more (9.82 ± 8.56) per performance than male ballet dancers (2.33 ± 4.66). A higher mean frequency of below shoulder lifts than above shoulder lifts was also noted, with the majority of above shoulder lifts remaining at eye level. Conclusion: Training programs must prepare dancers for upper body movements that consider differing biomechanical demands of a variety of lifts and inversions.